Bibliometric Exploration of Consumer Behavior towards Sustainable Products - Loso Judijanto; Andri Ardhiyansyah; Radityo Kusumo Santoso (West Science Social and Humanities Studies, 2024)
This research provides a comprehensive bibliometric analysis of consumer behavior towards sustainable products, examining key themes, research trends, and author collaboration networks from 1971 to 2024. The study identifies central themes such as consumer behavior, food and organic products, planned behavior, consumer perception, and strategic approaches, with a notable emphasis on the role of social media. Research trends indicate a significant focus on the food sector, particularly organic products, and a consistent interest in understanding the psychological and social factors driving sustainable consumption. The analysis also highlights potential future research areas, including deepening the understanding of consumer behavior, enhancing consumer perceptions, leveraging social media for sustainability promotion, and developing effective strategic interventions. The author collaboration network reveals strong co-authorship ties within distinct clusters of researchers, suggesting the need for increased cross-collaboration to enhance the field's breadth and impact. This study offers valuable insights for researchers, practitioners, and policymakers aiming to promote sustainable consumer behaviors and develop effective strategies for sustainability.